On the non-commutative main conjecture for elliptic curves with complex multiplication - Bouganis, Thanasis; Venjakob, Otmar (The Asian journal of mathematics, 2010)
International Press of Boston - publishers of scholarly mathematical and scientific journals and books
Gesehen am 14.02.2019